2016
DOI: 10.1021/acsami.6b07735
|View full text |Cite
|
Sign up to set email alerts
|

Narrow-Band Organic Photodiodes for High-Resolution Imaging

Abstract: There are growing opportunities and demands for image sensors that produce higher-resolution images, even in low-light conditions. Increasing the light input areas through 3D architecture within the same pixel size can be an effective solution to address this issue. Organic photodiodes (OPDs) that possess wavelength selectivity can allow for advancements in this regard. Here, we report on novel push-pull D-π-A dyes specially designed for Gaussian-shaped, narrow-band absorption and the high photoelectric conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 39 publications
2
63
0
Order By: Relevance
“…These values are fully compatible with applications such as colour imaging for consumer electronic devices, as well as more demanding applications, e.g., computer vision. Particularly successful implementations have relied on dedicated molecular design strategies, e.g., D-A molecules approaching the cyanine limit (FWHM EQE ≈90-100 nm) [120,126]. Additionally, two important schemes relating to aggregation effects in the solid state have emerged as highly effective for achieving NBA-type photodetection with EQE widths well below 100 nm.…”
Section: Impact Of Narrowband Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…These values are fully compatible with applications such as colour imaging for consumer electronic devices, as well as more demanding applications, e.g., computer vision. Particularly successful implementations have relied on dedicated molecular design strategies, e.g., D-A molecules approaching the cyanine limit (FWHM EQE ≈90-100 nm) [120,126]. Additionally, two important schemes relating to aggregation effects in the solid state have emerged as highly effective for achieving NBA-type photodetection with EQE widths well below 100 nm.…”
Section: Impact Of Narrowband Strategiesmentioning
confidence: 99%
“…Chloroboron subphthalocyanine (SubPc) is another small molecule that has delivered high phototransduction efficiency in a number of works, giving an EQE p of 62.6% in combination with DCV3T [58], and 60.1% in combination with quinacridone [58,61] (figure 7(b)). Newly synthesised small-molecule donors featuring a D-A structure approaching the cyanine limit have also yielded EQE values in the ≈50%-70% range in combination with fullerenes ( figure 7(b)) [120,126,128,129]. Finally, Li et al demonstrated the potential of a singlecomponent squaraine photoactive layer, achieving an EQE p as high as 66% [72].…”
Section: Green-selective Photodetectors (500-600 Nm)mentioning
confidence: 99%
See 1 more Smart Citation
“…Solution processable organic bulk‐heterojunctions (BHJs) or metal‐halide perovskites are in this respect interesting candidates, and several approaches to achieve wavelength‐selective photodetection using these materials have been recently proposed . For photoactive materials with tailored absorption spectra, high responsivities were achieved in the short‐wavelength regime (<700 nm), with a spectral full‐width at half‐maximum (FWHM) of the order of 100 nm . Narrower spectral responses were recently demonstrated through the use of thick active layers, resulting in carrier collection only for weakly absorbed wavelengths at the optical gap …”
mentioning
confidence: 99%
“…Over the past several years, extensive research on OPDs with color selectivity has been carried out. Most of this research, however, has focused on green‐ or blue‐selective OPDs, presumably because of the difficulties related to realizing red‐selective absorption of organic semiconductors. To expand the absorption spectrum of π‐conjugated organic compounds to 600 nm or higher, a largely delocalized conjugation structure should be introduced into the molecular structure.…”
mentioning
confidence: 99%